Answer:
The solution to the system is:
(x, y) = (-1, 1)
Step-by-step explanation:
Given the system of equations:
5x + 10y = 5 ..............................................................(1)
-13x + 4y = 17 ............................................................(2)
From (1)
5x = 5 - 10y
x = 1 - 2y .................................................................(3)
Substituting (3) into (2)
-13(1 - 2y) + 4y = 17
-13 + 26y + 4y = 17
Collect like terms
26y + 4y = 17 + 13
30y = 30
y = 30/30 = 1 .........................................................(4)
Substituting (4) into (3)
x = 1 - 2(1)
x = 1 - 2 = -1
Therefore the solution to the system is:
(x, y) = (-1, 1)